2020
DOI: 10.3390/microorganisms8050759
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Cold-Shock Response in the Extremely Acidophilic Archaeon, Cuniculiplasma divulgatum

Abstract: The archaeon Cuniculiplasma divulgatum is ubiquitous in acidic environments with low-to-moderate temperatures. However, molecular mechanisms underlying its ability to thrive at lower temperatures remain unexplored. Using mass spectrometry (MS)-based proteomics, we analysed the effect of short-term (3 h) exposure to cold. The C. divulgatum genome encodes 2016 protein-coding genes, from which 819 proteins were identified in the cells grown under optimal conditions. In line with the peptidolytic lifestyle of C. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…It revealed high confidence interactions with other subunits of DNA polymerase III (dnaE, dnaQ, holA) and proteins that have been described to be involved in replicative synthesis in bacteria. These interactions confirm the role of AUB74781.1 in DNA replication ( Bargiela et al, 2020 ). The protein AUB74810.1 explained as pyrimidine/purine nucleoside phosphorylase showed strong interactions with proteins associated with the purine salvage pathway.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…It revealed high confidence interactions with other subunits of DNA polymerase III (dnaE, dnaQ, holA) and proteins that have been described to be involved in replicative synthesis in bacteria. These interactions confirm the role of AUB74781.1 in DNA replication ( Bargiela et al, 2020 ). The protein AUB74810.1 explained as pyrimidine/purine nucleoside phosphorylase showed strong interactions with proteins associated with the purine salvage pathway.…”
Section: Resultssupporting
confidence: 81%
“…Additionally, cold adaptation in psychrophiles is attributed to membrane proteins, chaperones, RNA helicases, cold shock proteins, carotenoids, short- and branched-chain fatty acids, and antioxidative enzymes. Furthermore, an increase in the expression of proteins related to replication, transport, and folding was reported as a mechanism of cold adaptation ( De Maayer et al, 2014 ; Bargiela et al, 2020 ). Likewise, changes in the catalytic activity of the enzymes, changes in central metabolic activities, post-translational modifications, synthesis of storage polymers, like polyhydroxyalkanoates (PHAs) were reported to be advantageous for bacterial adaptation to cold temperatures ( Tribelli and Lopez, 2018 ; Bargiela et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Subbiah et.al on the classification rules for psychrophilic and mesophilic proteins showed that when the percentage of Ser and Thr is higher than certain values, the proteins would be classified as psychrophilic proteins ( Nath et al, 2012 ). Meanwhile, a pairwise comparison of proteins from cold-adapted archaea revealed that there was higher content of non-charged polar residues, especially threonine ( Berthelot et al, 2019 ; Bargiela et al, 2020 ). Ser and Thr are uncharged polar amino acids and prefer to reside on the surface of the psychrophilic proteins ( Jahandideh et al, 2007 ), therefore they tend to have more interactions with water molecules around proteins ( Sun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Lon proteases and serine proteases of S46 superfamily were detected, which are membrane-bound enzymes (Additional file 3 : Table S2) hydrolysing extracellular proteins for their assimilation and are very common in Thermoplasmatales [ 51 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%